The Influence of Customer Experience, E-Service Quality and E-Wom on E-Loyalty With Customer Satisfaction as an Intervening Variable - Ramadhanty, Nadine; Halik, Abdul; Prastiwi, Estik Hari (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
The development of digital technology has driven the rapid growth of e- commerce, making business people focus on improving service quality to meet customer needs. This trend emphasizes ease of shopping, speed of delivery, and variety of products offered to increase customer satisfaction and loyalty, or e-loyalty, which is an important indicator of e-commerce success. This research aims to analyze the influence of customer experience, e-service quality, and e-WOM on customer satisfaction and e-loyalty, especially in the context of online shopping, where consumer decisions are often based on digital information and virtual interactions. The population in this study are subjects related to the research the author conducted at UNTAG Surabaya, so the respondents of this study were UNTAG Surabaya students, especially the Faculty of Economics and Business. A total of 100 respondents were found using purposive sampling technique. Hypothesis testing in this research was carried out using a Structural Equation Model (SEM) approach based on Partial Least Square (PLS). Based on the analysis of 7 hypotheses, it was found that 5 hypotheses were accepted, and 2 hypotheses were rejected. From these findings it is concluded that customer experience, e-service quality, and e-WOM have a significant positive influence on customer satisfaction. Then, customer experience and customer satisfaction have a significant positive influence on e-loyalty. Meanwhile, e-service quality and e-WOM have an insignificant influence on e-loyalty.